Eighth grade bites eaudiobook The chronicles of vladimir tod. - Brewer, Heather (The Chronicles of Vladimir Tod, 2018)
Vlad has to keep his vampire urges under control while dealing with the pressures of middle school. Thirteen-year-old Vladimir Tod really hates junior high. Bullies harass him, the principal is dogging him, and the girl he likes prefers his best friend. Oh, and Vlad has a secret: His mother was human, but his father was a vampire. With no idea of the extent of his powers, Vlad struggles daily with his blood cravings and his enlarged fangs. When a substitute teacher begins to question him a little too closely, Vlad worries that his cover is about to be blown. But then he faces a much bigger problem: He’s being hunted by a vampire killer.